Culture and Media In Wartime and Post-War Period - Kalajžic, Vesna (Richtmann Publishing, 2012)
At the very beginning of the democratization of post-communist societies and European Integration, Republic of Croatia hasencountered a number of obstacles. The hardest period it went through was during the Homeland War. Culture represents an importantpart of human life, which is especially expressed in extraordinary situations such as war and post-war periods. Promoting cultural lifeduring and after the wartime is extremely valuable, especially through the media, which has an increasingly strong influence. The aim ofthis paper is to understand the role of newspaper in the context of culture in wartime and post-war years and widening the knowledgeabout the relationship between the newspaper and culture. The paper is based on articles about culture published in Zadar newspapersin the period from 1990 to 1996, collected with the reference to the programme of the Cultural Policy of the Republic of Croatia which,after adaptation to the newspaper corpus, includes: Literature and Publishing, Visual Art, Music, Performing Arts, Film, Media, CulturalHeritage – monuments, archives, libraries and museums. The result of the research were obtained by the analysis of 487 issues ofnewspapers and 2400 articles. The research consisted of qualitative and quantitative text analysis. The obtained data were processed inthe author's application ZD-newspaper explorer, developed by using the database management program Microsoft Access.